Indications and effectiveness of arthroscopic lavage and debridement in osteoarthritis knee - Srivastava, Neeraj; Khan, Shameem A.; Kumar, Vivek (International Journal of Research in Medical Sciences, 2019)
Background: Degenerative joint disease will afflict most of the people if they live long enough. The majority of patients with osteoarthritis present to orthopaedic surgeons seeking relief of pain and associated restoration of function. Various intraarticular and periarticular structures may be the cause of pain. Improvement in osteoarthritis by arthroscopic lavage and debridement is seen due to various mechanisms. Methods: In a prospective study from July 2016 to December 2018, 35 patients with primary osteoarthritis knee were assessed for effectiveness of arthroscopic lavage and debridement in relieving symptoms of osteoarthritis of knee and to determine the indications of arthroscopy in osteoarthritis of knee. Assessment was done using variables as age of the patient, body mass index, varus deformity, radiographic grading and arthroscopic grading. Results: A declining trend was seen on follow up over time; 91.4% excellent to good results seen at one month follow up, 76.1% at six months, 49.93% at twelve months, 37.5%, at eighteen months, 23.07% at twenty-four months and 28.5% at thirty months. Results at six month follow up when compared, were better for age less than 50 years (88.8% Vs 73.1% in >50 years age), normal weight patients with BMI 18.5 to 25(94.5% Vs 58.5% in overweight), varus angulation <100(93.1% Vs 0% in >100), radiological grade I and II (95-100% Vs 45-50% in grade III and IV) and arthroscopic grade I and II (94-100% Vs 0-77% in grade III and IV). Conclusions: Arthroscopic lavage and debridement is an effective method of treatment for osteoarthritis knee in patients with grade I and grade II osteoarthritis having symptoms of pain and locking due to loose bodies or degenerative meniscal tears.